The Dilemma for the new administrative culture in Mexican public administration: Esprit de Corps or individualist bureaucracy? - Arellano-Gault, David (2013)
Using empirical data from the first survey conducted with certified Civil Service Officials at the federal level in Mexico, this article discusses how a new administrative culture is already rising within this bureaucratic group. The Mexican civil service is a young institution; the law creating the sector was passed in 2003, after the dominant party that controlled the executive branch for more than 70 years (the PRI) lost the presidential elections for the first time in 2000. The general objective of the Civil Service Law of 2003 was to eliminate the spoils system, thus inaugurating a new era for Mexican public administration. However, this law seems to assume that a civil service is primarily a problem of "professionalization" of individuals, not recognizing any attempt to view the civil service as a group of persons developing a group morale and ethos. Still, this article argues that an esprit de corps is an inevitable outcome of the maturity of a civil service, and the Mexican case will not be the exception. - Reproduced.
Keywords: Public administration